Microbiome in cancer metastasis: biological insights and emerging spatial omics methods - Meyers, Marianne; Stoffels, Charlotte B. A.; Frache, Gilles; Letellier, Elisabeth; Feucherolles, Maureen (Frontiers in Cellular and Infection Microbiology, 2025)
The role of the microbiome in cancer metastasis has emerged as a critical area of research, with growing evidence suggesting that microbial composition and interactions within the tumour microenvironment may significantly influence metastatic progression. This review explores the role of the microbiome in cancer metastasis, as well as potential key bacteria and their mechanisms through which they could impact tumour dissemination, seeding and growth. Biological models used to study metastasis are discussed to provide context for the further investigation of these interactions. In order to answer unresolved questions regarding the microbiome’s involvement in metastatic dissemination, recent advancements in spatial biology techniques are examined, including spatial genomics, transcriptomics, proteomics and metabolomics, which enable the spatial mapping of microbial interactions within the tumour microenvironment. Additionally, multimodal-omics imaging approaches are highlighted for their potential to integrate multiple molecular layers, offering comprehensive insights into the microbiome’s role in cancer metastasis. The review also addresses the challenges and limitations of these techniques, underscoring the complexity of studying microbiome-tumour interactions and offering directions for future research to better explore and target the microbiological landscape in metastatic cancer.